Trans‐Specific Polymorphisms Between Cryptic Daphnia Species Affect Fitness and Behavior - Connor S. Murray; Madison Karram; David J. Bass; Madison Doceti; Dörthe Becker; Joaquin C. B. Nunez; Aakrosh Ratan; Alan O. Bergland (Molecular Ecology, 2025)
Shared polymorphisms, loci with identical alleles across species, are of unique interest in evolutionary biology as they may represent cases of selection maintaining ancient genetic variation post‐speciation, or contemporary selection promoting convergent evolution. In this study, we investigate the abundance of shared polymorphism between two members of the Daphnia pulex species complex. We test whether the presence of shared mutations is consistent with the action of balancing selection or alternative hypotheses such as hybridization, incomplete lineage sorting or convergent evolution. We analyzed over 2,000 genomes from six taxa in the D. pulex species group and examined the prevalence and distribution of shared alleles between the focal species pair, North American and European D. pulex . We show that North American and European D. pulex diverged over 10 million years ago, yet retained tens of thousands of shared polymorphisms. We suggest that the number of shared polymorphisms between North American and European D. pulex cannot be fully explained by hybridization or incomplete lineage sorting alone. We show that most shared polymorphisms could be the product of convergent evolution, that a limited number appear to be old trans‐specific polymorphisms, and that balancing selection is affecting convergent and ancient mutations alike. Finally, we provide evidence that a blue wavelength opsin gene with trans‐specific polymorphisms has functional effects on behavior and fitness in the wild.

Challenging Paradigms Around the Role of Colony Size, Taxa, and Environment on Bleaching Susceptibility - Mariana Álvarez‐Noriega; Eoghan A Aston; Madison Becker; Katharina E Fabricius; Will F Figueira; Sophie E Gordon; Ryan Krensel; Marine AA Lechene; Tiny Remmers; Maren Toor; Renata Ferrari (Global Change Biology, 2025)
Understanding how bleaching severity varies across space and among and within taxa helps predict changes in community composition due to climate change and informs conservation efforts. Photogrammetry offers a non‐invasive and time effective method for quantifying attributes of thousands of coral colonies across large, environmentally diverse reef areas. This approach circumvents the limitations of traditional survey methods, where detailed tracking of individual colonies comes at the expense of large sampling areas and sample sizes. Using photogrammetry, we measured colony size and scored bleaching severity of > 5000 colonies of 13 taxa across 26 sites (> 7400 m 2 of reef) during a mild bleaching event in the central Great Barrier Reef (GBR) in 2022. We quantified the relationship between bleaching severity and key biological and environmental factors: colony size, taxonomic identity, degree‐heating weeks (DHWs), water velocity, various measures of reef structural complexity, depth, and distance to coast. Our results show that bleaching probability decreased with increasing colony size for most taxa, contradicting the current understanding of size‐dependent bleaching. Counter to conventional thinking, tabular Acropora spp. presented very low levels of bleaching in 2022 despite being among the most severely bleached taxa during the bleaching event in 1998, suggesting possible adaptation in the last two decades. Our results show a high level of idiosyncrasy in environmental gradients of bleaching severity. For instance, the effect of depth on was taxon‐dependent and the effect of wave velocity differed between inshore and offshore reefs. Our results challenge prevailing paradigms around the role of colony size and environment in regulating bleaching susceptibility, suggesting that refugia are not universal but instead depend on specific environment‐taxonomic combinations and taxon‐specific colony sizes.